A Survey of the European Security Market - Carlos Martí Sempere (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This document synthesizes the results of the research made on the European security market. It deals with questions of interest regarding the provision of security goods and services for protecting society from terrorism and organised crime. It explores issues such as market revenues, demand and supply, industrial capabilities, technology, research and development, innovation, business strategies, competition as well as market structure, agents' conduct and economic performance. The research has been based upon desk analysis of open source information related to the security market. Economic theory and critical analysis has been applied to understand the gathered information, derive knowledge, point out key issues and assess trends and drivers that will likely shape the sector's future. The study is the outcome of the working package number 5 included in the research project A new Agenda for European Security Economics (EUSECON). This project with code number 218195 has been financed by the European Commission within the 7th European Research Framework Programme. The task has been performed by the company ISDEFE according to the scope and work plan described in the EUSECON proposal. The author wishes to express his appreciation to all the individuals that have provided input and valuable comments to this study, including anonymous referees. Any flaws or omissions contained in this document are solely the responsibility of the author.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330